White Matter Abnormalities in the Corpus Callosum in Acute and Recovered Anorexia Nervosa Patients—A Diffusion Tensor Imaging Study - Nickel, Kathrin; Tebartz van Elst, Ludger; Holovics, Lukas; Feige, Bernd; Glauche, Volkmar; Fortenbacher, Tina; Endres, Dominique; Zeeck, Almut; Tüscher, Oliver; Joos, Andreas; Maier, Simon (Frontiers in Psychiatry, 2019)
Objective: Severe and persistent malnutrition in patients with anorexia nervosa (AN) leads to pronounced structural brain changes whose reversibility after recovery is currently unclear. Previous diffusion tensor imaging (DTI) studies investigating white matter (WM) microstructure alterations in AN are inconsistent. Methods: In this so far largest DTI study in adults, we investigated 33 AN patients, 20 recovered and 33 healthy women. DTI data was processed using the “DTI and Fiber tools” and the Computational Anatomy Toolbox (CAT12). WM integrity both, in terms of fractional anisotropy (FA) and mean diffusivity (MD), was assessed. Results: We found a significant FA decrease in the corpus callosum (body) and an MD decrease in the posterior thalamic radiation in the AN group. The REC group displayed FA decrease in the corpus callosum in comparison to HC, while there were no MD differences between the REC and HC groups. Conclusion: Despite prolonged restoration of weight in the REC group, no significant regeneration of WM integrity in terms of FA could be observed. Transient changes in MD may represent a reversible consequence of the acute state of starvation or result from dehydration. Reduction of FA either may be due to WM damage resulting from malnutrition or may be considered a pre-morbid marker.